Saucerization versus dissection on the repair of vesicovaginal fistulae - Umoiyoho, Aniefiok J.; Olatunbosun, Olujimi Abiona (Family Medicine & Primary Care Review, 2017)
Background . An obstetrics fistula is both an unfortunate and annoying preventable complication that follows poorly managed prolonged obstructed labor. Despite an improvement in obstetric management, this condition has remained with us in developing countries partly because of the failure of effective maternity care, as well as lack of adequately trained surgeons to repair the backlog of cases. Objectives . This study was therefore designed to determine whether a simpler and quicker method of fistula repair – saucerization – could be recommended for fistula repair by relatively inexperienced surgeons as compared to the more technical dissection method, which requires a higher level of surgical expertise. Material and methods . This was an intervention analytical study of 77 fistula repairs done between 2010 and 2013 using either saucerization or dissection methods. The success (closure) rate for each method was calculated. A test of association between surgical technique and outcome of surgery using the chi-squared test was done. Residual fistulae dimensions and degree of scarring were assessed and analyzed using SPSS version 20. Results . The dissection method had a higher, though not statistically significant, cure rate than the saucerization method (92.3% vs 76.3%, p = 0.053). Residual fistulae dimensions were larger in the saucerization group, while fibrosis was higher in the dissection method. Conclusions . The saucerization technique for the repair of VVF was inferior to the dissection method, although the difference in cure rate was not statistically significant.